IDENTITY AND ACCESS MANAGEMENT ACCORDING TO THE IMPLEMENTATION OF THE SIMOIT PROJECT AND TNC@FHH - Eren, Evren; Detken, Kai-Oliver (International Journal of Computing, 2010)
This paper considers some of the identity and access management mechanisms, and adds to this the new requirements posed by identity management in mobile ubiquitous environments. The authors present the state-of-the-art in identity management standards and initiatives in the context of the SIMOIT project and the TNC@FHH implementation. Furthermore, the paper discusses the results achieved by these projects with respect to the generic requirements in different scenarios and compares the achievements.